Comparative Analysis of Characteristics of Modified Masonry Unit with Infused Additives: Coal, RHA, and Sawdust - Chhetri, Saurav Kuwar; Thapa, Rija; Bhusal, Gaurav; Kharbuja, Sunita (International Journal on Engineering Technology, 2026)
Brick is one of the most commonly used construction materials. The performance, age, and economy of a project are hugely impacted by brick characteristics. This study aimed to investigate the behavior of modified bricks in terms of compressive strength, porosity, and economic perspectives. Fifteen brick formulations were investigated: a Coal-based series (five variants: 2–10% coal by weight), RHA+Sawdust combinations (four variants with varying RHA:SD ratios totaling 8%), a Sawdust-only series (four variants: 2–8% sawdust), and reference samples (Traditional Dachii Appa and Modern machine-made bricks). All specimens were tested in the laboratory as per IS 3495:1992 for compressive strength, water absorption, porosity, bulk density, and durability. Compressive strength was enhanced by adding 6% coal, yielding 8.282 MPa; the RHA+SD combination of 6% RHA and 2% SD achieved the highest modified-brick strength of 9.662 MPa. All formulations met the minimum strength requirement (≥ 3.5 MPa) of NBC 109:1994. The average water absorption of coal-based bricks was 20.359%, with an average group porosity of 29.469%, whereas the RHA+SD group showed an average porosity of 36.189% (individual values ranging up to 39.3%) with enhanced strength but higher porosity. By integrating industrial and agricultural by-products into bricks, structural integrity can be maintained while achieving sustainable solutions for brick manufacturing. Additionally, these bricks contribute to resource efficiency and eco-friendly building practices in the Nepalese construction industry.